New distributional records of spiders (Arachnida: Araneae) from the west coast of peninsular Malaysia - Nasir, D.M.; Su, S.; Mohamed, Z.; Yusoff, N.C. (Zoological Society of Pakistan, 2014)
This study documented an additional of 219 spider species to the previous checklist of Peninsular Malaysia. Species recorded comprised of field specimens and lists obtained from available literatures. For field specimens, spiders were collected from 11 different locations in west coast of Peninsular Malaysia between January 2012 through December 2013. A total of 70 spider species from field collection were considered as new records while the other 149 spider species were compiled from available literatures. This documentation added up to a total of 644 spider species currently recorded in Peninsular Malaysia.